2022
DOI: 10.1186/s13690-022-00956-6
|View full text |Cite
|
Sign up to set email alerts
|

The CIVISANO protocol: a mixed-method study about the role of objective and perceived environmental factors on physical activity and eating behavior among socioeconomically disadvantaged adults

Abstract: Background Overweight and obesity have a strong socioeconomic profile. Unhealthy behaviors like insufficient physical activity and an unbalanced diet, which are causal factors of overweight and obesity, tend to be more pronounced in socioeconomically disadvantaged groups in high income countries. The CIVISANO project aims to identify objective and perceived environmental factors among different socioeconomic population groups that impede or facilitate physical activity and healthy eating behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 132 publications
(193 reference statements)
0
5
0
Order By: Relevance
“…Thus, for the HSES group, a higher density of unhealthy food outlets were associated with a lower consumption frequency of SSBs. This contrasts with prior studies, possibly due to differences in supermarket inclusion and also since SSBs are reportedly most often bought at convenience stores; this type of food outlet is scarce in peri-urban settings [ 40 ].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Thus, for the HSES group, a higher density of unhealthy food outlets were associated with a lower consumption frequency of SSBs. This contrasts with prior studies, possibly due to differences in supermarket inclusion and also since SSBs are reportedly most often bought at convenience stores; this type of food outlet is scarce in peri-urban settings [ 40 ].…”
Section: Discussionmentioning
confidence: 70%
“…In this cross-sectional study, data from respondents in the CIVISANO project was used, a mixed-methods study investigating the role of objective and perceived environmental factors on physical activity and eating behavior among adults residing in two medium-sized peri-urban municipalities, Duffel and Herselt, in Flanders, Belgium [ 40 ]. The study was approved by the Medical Ethics Committee of Ghent University Hospital (BC-248 09260) and conducted in accordance with the recommendations of the Belgian Data Protection Authority.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of the CIVISANO-project, a research project using mixed-methods to investigate the role of objective and perceived environmental factors in PA and eating behaviors among PSEDS in two peri-urban municipalities in Belgium. A detailed description of the complete study protocol can be found elsewhere ( D’Hooghe et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, other recruitment strategies were also employed such as posting QR-codes to ll in the questionnaire in traditional (local) media and social media and making the questionnaire available in local places such as libraries and medical o ces. Full study details are available elsewhere (25). This recruitment strategy resulted in a study sample of 498 respondents.…”
Section: Study Samplementioning
confidence: 99%